279 Evaluation of Green Grass Inclusion on Digestibility and Fatty Acid Flow in Finishing Diets of Beef Cattle. (7th May 2021) - Wiseman, Aksel; Spore, Tyler; Norman, Mitch; Wilson, Hannah; MacDonald, James C; Watson, Andrea K; Erickson, Galen E
Abstract: Six ruminally and duodenally cannulated steers were utilized in a 3 × 3 replicated Latin square experiment to determine duodenal fatty acid (FA) flow. Treatments consisted of 3 levels of Green Grass (GG, Sunseo Omega 3; Chungcheong Duk-Do, South Korea), a feed comprised of sesame meal, giant kelp, cassava, and sorghum, at 0, 15, and 30% of diet DM. Data were analyzed using the MIXED procedure of SAS with treatment and period as fixed effects and animal as a random effect. There were no differences in DMI, organic matter (OM) intake, total tract DM or OM digestibility (P ≥ 0.16). Intake of NDF and ADF increased linearly (P < 0.01) from 0 to 30% GG inclusion. Total tract digestibility of NDF was the poorest (P ≤ 0.02) for GG0 with no differences between GG30 and GG15 (P = 0.33). Total tract ADF digestibility was poorest for GG30 (P < 0.01) while GG0 and GG15 were not different (P = 0.17). Fatty Acid values were reported as relative abundance of the total FA present in duodenal samples. The lowest (P < 0.01) concentration of saturated FA was GG30 (70.3%) while GG0 and GG15 were not different (P = 0.83; 78.2%). The concentration of unsaturated, mono-unsaturated, poly-unsaturated, and trans FA responded quadratically (P < 0.01) with no difference between GG0 and GG15 and increasing to GG30. Omega-6 FA tended to decrease linearly (P = 0.06) from 0 to 30% GG inclusion (4.91 and 3.85 g/d, respectively). Omega-3 FA increased linearly (P < 0.01) from 0 to 30% GG inclusion (1.84 and 10.78 g/d, respectively). These data suggest increasing inclusion of GG up to 30% of diet DM does not affect DM or OM digestibility. Greater inclusions of GG resulted in more unsaturated and omega-3 FA concentrations in the duodenum.